JORDAN-YOUNG, Rebecca; KARKAZIS, Katrina. 2019. Testosterone: an unauthorized biography. Cambridge: Harvard University Press. 288p. - Marina Fisher Nucci (Sexualidad, Salud y Sociedad: Revista Latinoamericana)
Reseña: JORDAN-YOUNG, Rebecca; KARKAZIS, Katrina. 2019. Testosterone: an unauthorized biography. Cambridge: Harvard University Press. 288p.